A DESCRIPTIVE STUDY IN TEACHING READING REPORT TEXT AT THE NINTH GRADE OF SMPN 24 BANJARMASIN - Haryani, Istina Dewi (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2019)
The purpose of the research to find out the strategy, method, technique, material and the evaluated in teaching reading report text at the ninth-grade students of SMP Negeri 24 Bjm. The qualitative descriptive research was used by researcher. English teachers who teach SMPN at the ninth grade. Observation sheet, interview and documentation was used instrument by the teacher. To see whether the teaching and learning reading report text is the purpose of observation sheet. To get specific information in teaching reading report text is the function of interview. The syllabus, lesson plans and the material control are part of documentation. The findings of this research are the teacher’s strategy in teaching reading report text is used memorizing, question answer relationship and discussion. Grammar translation method and direct method were method used by the teacher. Three phase technique, QARs, and SQ3R technique. Multiple choice, fill in the bank and true false was used teachers evaluated to students. Describing person, animal, plant and so on in general was material of report text. The ways to determine learning goals during teacher learning process was the strategy applied by the teacher.